PENGARUH ASAM SALISILAT TERHADAP KANDUNGAN FLAVONOID PADA KULTUR KALUS GINSENG JAWA (Talinum paniculatum (Jacq.) Gaertn.) - Matthew Linardi; Ratih Restiani; Dwi Aditiyarini (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
Javanese ginseng (Talinum paniculatum) is a plant that is used as raw material in traditional medicine because it contains flavonoid as one of it’s secondary metabolites. Increasing the flavonoid content in Talinum paniculatum can be done by applying elicitation to in vitro culture. Salicylic acid is an abiotic elicitor that is often used in elicitation because it can increase the production of secondary metabolites. The aim of this study was to determine the effect of salicylic acid concentration and elicitation time on callus biomass and flavonoid content in Talinum paniculatum callus culture. Talinum paniculatum callus production was carried out on MS medium with a combination of 2 mg/L 2-4,D and 3 mg/L kinetin. Elicitation was carried out on callus that had entered the stationary phase on the interaction of variations in the concentration of salicylic acid concentrations of 5 ppm, 10 ppm, 15 ppm, and 20 ppm and elicitation times were 2 days, 4 days, and 6 days. Each variations were replicated three times. The callus was dried and extracted and then the flavonoids were identified and measured semi-quantitatively using thin layer chromatography (TLC). The callus biomass elicited by varying the concentration of salicylic acid and elicitation time (0.052 – 0.067) was not significantly different from the control (0.067). The most optimal concentration and elicitation time were found at 20 ppm salicylic acid concentration and 2 days elicitation time with the largest flavonoid stain area (1.570 cm2), color intensity 3, and Rf value similar to control (0.5).